Validation of new automated turbidimetric immunoassays for the measurement of haptoglobin and inter‐α‐trypsin inhibitor heavy chain H4 specific for the bovine species. (3rd November 2022) - Bassols, Anna; Robles‐Guirado, José Angel; Arroyo, Laura; Soler, Lourdes; García, Natalia; Pato, Raquel; Peña, Raquel; Saco, Yolanda; Armengol, Ramon; Lampreave, Fermín; Alava, María A.; Canalias, Francesca; et al.
Abstract: Background: Good strategical programs are required for the early detection of disease even in the absence of evident clinical signs, which is crucial in satisfying animal welfare. Haptoglobin (Hp) and inter‐α‐trypsin inhibitor heavy chain H4 (ITIH4) are acute phase proteins and good biomarkers of early inflammation in cattle, with plasma levels that significantly increase after injury or infection. Objectives: We aimed to develop and validate two new immunoturbidimetric methods for Hp and ITIH4. Methods: Species‐specific antibodies were obtained and used to develop the immunoassays. For the Hp assay, antibodies were fixed to latex microparticles to enhance detection. The immunoassays were set up in an automated analyzer to carry out validation studies. Reference intervals were calculated using Reference Value Advisor. Results: The Hp immunoturbidimetric method had a linear analytical range up to 0.40 mg/mL. The limit of detection (LoD) was 0.005 mg/mL, and the limit of quantification (LoQ) was 0.007 mg/mL. Total imprecision was less than 7%. Comparison with ELISA and single radial immunodiffusion (SRID) showed good correlation, whereas the comparison with the colorimetric method showed constant and proportional differences. The ITIH4 immunoassay showed linearity up to 5 mg/mL, and the LoD was 0.002 mg/mL. Total imprecision was less than 6%. Method comparison showed a good correlation with single radial immunodiffusion, both methods being equivalent. Bilirubin, triglycerides, and hemoglobin presented no interference in any of the assays. Reference intervals were 0.007‐0.017 mg/mL for Hp and 0.2‐0.7 mg/mL for ITIH4 in dairy cows 10 days before parturition. Conclusions: Immunoturbidimetric methods developed for Hp and ITIH4 can measure basal and increased levels of these proteins, showing adequate precision, accuracy, and robustness.